PEMBENAHAN STRUKTUR GAJI KARYAWAN KEDAI ABC DI KOTA BOGOR MENGGUNAKAN METODE POINT SYSTEM - Naisha Afina Salsabila; Muthiar Rahmah; Khairunisa Suci Arivia; Muhammad Nashiruddin An-Nadwi; Muhamad Satibi; Lindawati Kartika (Jurnal Pijar, 2023)
The compensation system is an important component of an organization in optimizing employee performance and job satisfaction. Based on this, a research was conducted on the ABC Shop located in Bogor City. The sample in this study is the entire ABC Shop employee salary data with a total of 23 employees. This study aims to evaluate and improve Kedai ABC's compensation system. Source of data obtained from primary data and secondary data. The primary data collection technique was carried out through distributing questionnaires and direct interviews with the General Manager of the ABC Shop. While secondary data obtained from literature study. Compensable factors are determined using the hay system approach, job grading is determined using a given grade, and salary structure is using the point system method. The results of this study indicate that the basic salary of Kedai ABC after improvement is still below the minimum wage. However, the salary intervals at each level are not too far apart or close together. This is in accordance with the point system method so that this method can be used to determine the wages of the employees of the ABC Store ideally.